“Super-Short-Term” Study Abroad in Japan: A Dramatic Increase - Shimmi, Yukiko; Ota, Hiroshi (International Higher Education, 2018)
In recent years, there has been a dramatic increase of Japanese students participating in “super-short-term” study-abroad programs, lasting from one week up to one month. This reflects a growing global trend among college students, especially in developed countries. This article discusses the background of this trend in Japan as well as emerging challenges.